Popular : a novel - Grosso, Alissa (Mumbai : Jaico, 2013)
Told from their different viewpoints, Fidelity High seniors Olivia, Zelda, Nordica, and Shelly observe their clique, the elite entourage of popular Hamilton Best, crumbling due to lies and secrets, including one that could destroy Hamilton's world.
Keywords: Young adult fiction; Cliques Fiction; High schools Fiction